ANÁLISIS CRÍTICO DE LA CARTOGRAFÍA HISTÓRICA DEL VALLE DEL RÍO NEGRO - Anahí Membribe (Boletín Geográfico)
The maps contain different conceptualizations of geographic space, so is possible to say that maps implicitly express ideas, desires, perspectives and priorities on a given territory; and therefore constitute clear power tools. The selection of the cartographic documents on which this analysis is sostained on the idea that each map holds a certain view of the territory, and also expresses the degree of development of mapping techniques used in each historical moment. In production, reading and interpretation of mapping take place the ideological and sociocultural context in which both the cartographer and the reader are involved. Thus, maps are never neutral, on the contrary, are a constructed reality, therefore confirmthat cartography represents the space, and also produces it.